Analisis Ketahanan Tanah berdasarkan Kecepatan Gelombang Geser (VS) di Kawasan Aliran Sungai Muara Bangkahulu Bagian Hilir, Kota Bengkulu - Purwaningsih, Annisa Indah; Mase, Lindung Zalbuin; Hardiansyah; Misliniyati, Rena; Supriani, Fepy (Universitas Negeri Gorontalo, 2025)
The downstream area of the Muara Bangkahulu River is a developing area in Bengkulu City that was affected by major earthquakes in 2000 and 2007. The risk of earthquake-induced damage in this area requires further investigation, particularly regarding soil resistance to seismic shaking. This study aims to analyze soil characteristics based on shear wave velocity (VS), site classification, and Ground Amplification Factor (GAF) to support earthquake-resistant infrastructure planning. This study uses microtremor data inversion methods conducted at 38 measurement points. Shear wave velocity (VS) data at depths of 10–50 m were analyzed to determine site classes and Ground Amplification Factor (GAF). Data processing was performed using surface wave inversion techniques to map VS distribution and seismic amplification. The results of the study show that VS values at depths of 10–50 m vary between 160–960 m/s, with site class classifications dominated by categories C (hard soil) and D (medium soil). The Ground Amplification Factor (GAF) values ranged from 1.1–1.9, with areas of high amplification indicating greater vulnerability to earthquake shocks. These findings serve as an important reference for disaster mitigation planning and earthquake-resistant infrastructure development in the region. Technical recommendations are needed for locations with high amplification to minimize the risk of earthquake damage in the future.